CULTURAL RICHNESS OF OSING AS A MAIN ATTRACTION FOR SUSTAINABLE TOURISM IN KEMIREN VILLAGE, BANYUWANGI - Rosita, Putri Aulia; Amalia Nur Savitri, Firdha; Akkapin, Supaphorn (Penerbit Lafadz Jaya, 2024)
The richness of Osing culture in Kemiren Village has positioned this site as a notable cultural tourism destination. This article aims to: 1) describe the tourist attractions in the Osing Traditional Cultural Village of Kemiren, Banyuwangi; 2) identify sustainable tourism development in this village; and 3) analyze the challenges faced in achieving sustainable tourism. Utilizing a descriptive qualitative research approach, this study employs observation and interview techniques to gather data. Findings indicate that sustainable tourism development in Kemiren Village is progressing positively, evidenced by economic, socio-cultural, and environmental benefits. However, certain obstacles persist, posing challenges to further advancements in sustainable tourism growth.